An exploratory study to assess stakeholder’s perception for new online teaching-learning environment during covid-19 - et. al., Sandeep Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Certain events bring unprecedented changes for the way things take place in our life. Spread of COVID-19 has brought a paradigm shift in a similar manner to the way we learn things and has dramatically altered the teaching learning process. Like any other tool, online learning was considered to be a supporting hand for augmenting the teaching learning experience by making the learning process more interactive and participative. COVID-19 has made online teaching as the sole mode for teaching learning for students and teachers. Without any doubt, when we run out of options only then we can ascertain the true facets of something. It can also be applied to evaluate the effectiveness of online teaching over traditional teaching. The present study is an endeavor to assess the stakeholder’s perception for this new teaching learning environment which has emerged during this unprecedented situation. Respondents were selected using stratified judgment sampling method. 120 respondents from Delhi NCR were interviewed using structured questionnaire. Statistical tools like factor analysis, cross tabulation, t-test and discriminant analysis were used for data analysis. Factor analysis led to formation of dimensions namely awareness related to online teaching learning process, perception for decisions taken by higher education bodies, impact of pandemic on economic conditions and subsequent attendance and effectiveness of online classes. Further two-group discriminant analysis was applied to find out association among predictors and effectiveness of online learning. It was observed that awareness related to online teaching learning process, perception for decisions taken by administration, impact of pandemic on economic conditions, attendance, socio-economic background were prominent factors which significantly affect the respondent’s perception for effectiveness of online classes.